PERAN SALES PROMOTION MELALUI IKLAN DI MEDIA SOSIAL TERHADAP PERILAKU KONSUMEN - Ade Irfaannumilah (Universitas Trunojoyo Madura, 2017)
The growing era of globaisasi trigger the rapid use of various kinds of teknonogi and information in everyday life.Begitupun influence is very impact on marketing activities in dunia.Berbagai kinds of marketing strategies used by companies to improve the marketing of products / services company, by utilizing various marketing mix as strategies used by the company. In this study the author will discuss about the role of sales promotion through advertising in social media to consumer behavior. The purpose of this study is to find the influence of the role of sales promotion through advertising in social media to consumer behavior. In this study the authors to find a very significant relationship related to sales promotion through social media advertising on consumer behavior where the results of sales promotion through this ad gives effect to the behavior consumers in deciding purchase decisions.